A Circular Framework for Evaluating Highway Construction Projects Success: AHP Approach - Ahmed Yousry Akal; Ahmed Ebrahim Abu El-Maaty; Saad Abdel-Karim El-Hamrawy (Salehan Institute of Higher Education, 2016)
Success has always been the ultimate goal of every activity, and a construction project is no exception. There are few topics in the field of project management that are so frequently discussed and yet so rarely agreed upon as that the notion of project success criteria. Usually much of the national budget on infrastructure development is channelled to highway construction projects. However, no official studies have been presented before to evaluate the performance this industry in Egypt. Consequently, this reflects the importance of this study which aims at laying out a standard framework which identifies the criteria for measuring projects success. The identified criteria, in turn, can be used as a tool to help the stakeholders of the highway projects in Egypt in judging the project performance and success during the project's post-construction phase. Using a detailed literature review thirteen success measures are identified (four objectives and nine subjective). Furthermore, the analytic hierarchy process (AHP) is adopted to prioritize the identified measures based on accumulative knowledge of academic experts in highways construction industry through the application of questionnaire survey. The study establishes that project completed on time, project completed within budget, health, safety and number of accidents, profitability and quality in construction are the most significant measures used for assessing the highway projects performance and success.